The The Potential Implementation of Biomass Co-firing with Coal in Power Plant on Emission and Economic Aspects: A Review - Meiri Triani; Fefria Tanbar; Nur Cahyo; Ruly Sitanggang; Dadan Sumiarsa; Gemilang Lara Utama (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Applying coal-biomass co-firing power generation is the strategy to accelerate the renewable energy share in the energy mix to reach 23% by 2025. Although biomass co-firing trials have been carried out at several Coal-Fired Power Plants (CFPP), the potential for implementing biomass co-firing on a larger scale and for the long-term propose still needs to be identified. This article evaluates emission characteristics and economic aspects of implementing biomass and coal in power plants. The traditional review method is used by identifying journal articles as data sources and further elaborating according to the context of the study. The primary emissions from co-firing biomass with coal contain CO, SO2, NOx, and particulate matter. The coal-biomass co-firing power generation has been widely adopted due to its various positive effects. However, it is still necessary to consider the cost of retrofitting, OM, biomass prices, and incentives in its application.